Extraction and Classification Feature of Timbers texture with Wavelet, Color Moment, and Multi Layer Perceptron - Rahayu, Putri Nur; Rakhmadi, Ardhon; Puji Putra, Anggarjuna Puncak; Erwanto, Danang Erwanto; Atmiasri, Atmiasri (WAHANA, 2026)
The manual identification and classification of timber species are often subjective, time-consuming, and require specialized expertise. To address these limitation, an automated system is essential to simplify the identification and classification processes. This research is combined approach to timber feature extraction based on texture and color. The three methods used are: 1) The method of Wavelet for spatial texture extraction, 2) The color moment method for extraction statistical color information (mean, standard deviation, and skewness), and 3) the Multi Layer Perceptron Method, where Multi Layer Perceptron is used to classify the extraction result from Wavelet and color moment